Development of Higher Vocational Education in Shuangcheng Economic Circle of Chengdu-Chongqing area Evaluation and Research on Coupling and Coordination with Economic Growth - Gong, Jian; Zhang, Qian (Journal of Theory and Practice of Social Science, 2024)
Objective: The Central Committee's meeting on the Chengdu-Chongqing economic plan highlights the role of higher vocational education in fostering technological progress and economic growth through skilled talent cultivation, aligning with the region's development opportunities. Methods: This paper uses entropy method and coupling coordination degree model to conduct empirical research on the collaborative development of higher vocational education and regional economy in Chengdu-Chongqing region from 2011 to 2020. Conclusions: 1) For Chengdu-Chongqing area, the coupling coordination degree has gradually changed from the original low level coupling coordination type to the good coordination degree.2) In order to maintain the balanced development of higher vocational education with economic and social development, our country must accelerate the transformation of government functions, promote the reform of vocational education, and promote the coordinated development of higher vocational education and regional economy.